The reception of the theory of Science in Jean Paul - Ferraguto, Federico (Discurso, 2017)
In this paper will be highlighted some aspects that characterize the Jean Paul Richter´s reception of Fichte's Wissenschaftslehre in the text of 1800 Clavis fichtiana seu leibgeberiana. This work represents a set of the first criticisms toward Fichte´s theory of knowledge and plays an important historical role in the identification between idealism and nihilism, developedby Jacobi in the Letter to Fichte of 1799. After a presentation of the genesis and Jean Paul’s critique to Fichte, the paper discuss the speculative core that motivates criticisms of Jean Paul, both in theoretical and practical perspective: the status of no-I as produced by an imaginative fiction.